Ten‐minute chat. (24th May 2014) - Batson, Emma
Abstract : Emma Batson is business manager at XLEquine. She has always had an interest in horses and, after a brief spell working with young racehorses in New Zealand, completed a PhD in equine physiology at the Royal Veterinary College, before working in industry.